2021
DOI: 10.1007/s10452-021-09841-w
|View full text |Cite
|
Sign up to set email alerts
|

Annual patterns of litter decomposition in the channel and riparian areas of an intermittent stream

Abstract: Intermittent streams, dominant in arid and semi-arid regions, are suggested to be more representative of the global river network than perennial rivers. Even so, the impacts of constant changes in hydrological regime on the functioning of these streams and riparian areas remain to be elucidated. In this study, two native deciduous litter species were used to compare microbialdecomposition patterns between the channel of an intermittent stream and its riparian area over one year. Overall, the stream channel pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Furthermore, the increasingly frequent occurrence of low-flow phases and dry events in a wide variety of streams and rivers worldwide has emphasized the need to understand how in-stream microbial communities respond to changing flow conditions. Desiccation due to the absence of flowing water can affect stream microbial communities associated with leaf decomposition, by delaying or severely retarding it, thus disrupting heterotrophic energy pathways [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the increasingly frequent occurrence of low-flow phases and dry events in a wide variety of streams and rivers worldwide has emphasized the need to understand how in-stream microbial communities respond to changing flow conditions. Desiccation due to the absence of flowing water can affect stream microbial communities associated with leaf decomposition, by delaying or severely retarding it, thus disrupting heterotrophic energy pathways [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that the chemical properties and nutrient status of leaves are important factors affecting the rate of foliage decomposition in rivers (Gessner et al, 2010;Alvim et al, 2015). In addition, abiotic factors such as hydrological regimes also significantly affect foliage decomposition (Anderson and Smith, 2002;Sun et al, 2012;Simões et al, 2021). Different flooding conditions often produce different physical and chemical environments (Behzad et al, 2022), which in turn regulate the decomposition rate of leaves (Anderson and Smith, 2002;Xie et al, 2016;Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%